An Intelligent Framework for Website Usability - Alexiei Dingli; Sarah Cassar (Advances in Human-Computer Interaction)
With the major advances of the Internet throughout the past couple of years, websites have come to play a central role in the modern marketing business program. However, simply owning a website is not enough for a business to prosper on the Web. Indeed, it is the level of usability of a website that determines if a user stays or abandons it for another competing one. It is therefore crucial to understand the importance of usability on the web, and consequently the need for its evaluation. Nonetheless, there exist a number of obstacles preventing software organizations from successfully applying sound website usability evaluation strategies in practice. From this point of view automation of the latter is extremely beneficial, which not only assists designers in creating more usable websites, but also enhances the Internet users’ experience on the Web and increases their level of satisfaction. As a means of addressing this problem, an Intelligent Usability Evaluation (IUE) tool is proposed that automates the usability evaluation process by employing a Heuristic Evaluation technique in an intelligent manner through the adoption of several research-based AI methods. Experimental results show there exists a high correlation between the tool and human annotators when identifying the considered usability violations.